Google Trends data reveal a sharp trend: teeth and claws attract more interest than feathers, hooves or fins. (25th June 2022) - Holmes, Branden; Strzelecki, Artur; Springer, Steffen; Zieger, Michael
Summary: In nature conservation, the generation of public interest, attention or emotions is an important instrument for nature, biotope and species protection; in this, charismatic flagship species play an important role. In the present study, flagship-making affiliation to a taxonomic unit as well as morphological, ecological and conservation traits were identified by analysing vertebrate species from each of the five extant vertebrate classes (Mammalia, Aves, Reptilia, Amphibia and fishes). Google Trends data on the 20 most Googled species of each of the five classes were used, a representation index was derived and the body mass, diet and protection status of these species were analysed. A clear concentration of interest in mammalian species was evident with the help of the introduced representation index. Furthermore, species with a higher body mass were clearly overrepresented in the data. Overall, important patterns in the studied traits were determined: belonging to Mammalia, a large body mass and a carnivorous diet are frequently represented among these species. For conservation purposes, such popular species can be specifically selected as flagship species or ambassadors to help protect entire biomes, which will therefore benefit less charismatic species as well. Possible ways to use traits that are perceived to be flagship-making in order to further the global conservation endeavour are briefly discussed.